Against ethics : contributions to a poetics of obligation with constant reference to deconstruction - Caputo, John D. (Studies in Continental thought., 1993)
John D. Caputo undertakes a passionate, poetic, and satiric search for the basis of an ethics in the postmodern situation. Caputo defends the notion of obligation without ethics, of responsibility without the support of ethical foundations.